The Erasure of Blackness and Shortcomings Within the Early Learning and Care Sector in Canada: Recommendations for the Way Forward - Kissi, Evelyn; Ewan, Anita (Journal of Childhood Studies, 2023)
This article critically examines the domain of early learning and care (ELC) in Canada, often termed early childhood education or early childhood studies. We delve into the Canadian ELC landscape, focusing on identified gaps in antibias education, especially concerning African/Black families. Drawing from a comprehensive literature review, we highlight disparities faced by African/Black children and families compared to their white and other racialized peers in the Canadian child welfare system. We conclude with six actionable recommendations to bridge these gaps, emphasizing collaboration among all stakeholders.